The geography of stock exchanges in Imperial Germany - Carsten Burhop; Sibylle H. Lehmann-Hasemeyer (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2014)
23 Stock Exchanges were in operation in Germany in 1913. We provide new data about the number of listed firms, their market value, and the number of IPOs between 1897 and 1913 for all exchanges. We assess reasons why a firm opts to be listed at a certain exchange. Large firms tend to be listed and tend to go public at the Berlin Stock Exchange, while the regional stock exchanges were important hosts for small and medium-sized firms. Borders and distance affect listing decisions, suggesting that a patriotic home bias and asymmetric information between issuer and investors affected listing decisions.
urn:nbn:de:bsz:100-opus-9834
Keywords: N23; G23; R12; 330; Financial development; Regional stock exchanges; IPOs; Germany; Economic history